The Effect of Financial Literacy and Financial Technology on Financial Performance (Case Study: Desa Kebun Kelapa ) - Geby Citra Ananda; Annisa Ilmi Faried; Maya Syaula; Irvan Malay (Yayasan Multidimensi Kreatif, 2023)
This study aims to analyze the effect of Financial literacy and Financial technology on financial performance in Desa Kebun Kelapa . Financial performance information is indispensable in assessing potential changes in economic resources to predict the production capacity of available resources. Fintech is a combination of financial services and technology, which allows financial transactions without having to have a bank account, on the one hand this creates problems for Indonesian people who are not ready to accept changes in economic activity, Through Financial Literacy and Financial Technology, it can help village officials in terms of improving their village's financial performance. This research is quantitative and the research data used are primary data and skunder. The object of research in this study is the village community of coconut plantations, especially business actors and village officials. The analysis method used is quantitative with an associative approach. The results showed that Financial Literacy and Financial Technology play an important role in improving village financial performance in the form of increased operational efficiency, and efficiency enjoyed by its members, however, the application of Financial Literacy and Fianncial Technology also has its own challenges.